2021
DOI: 10.1038/s41598-021-87482-7
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the signal-to-noise of low-field MRI with deep learning image reconstruction

Abstract: Recent years have seen a resurgence of interest in inexpensive low magnetic field (< 0.3 T) MRI systems mainly due to advances in magnet, coil and gradient set designs. Most of these advances have focused on improving hardware and signal acquisition strategies, and far less on the use of advanced image reconstruction methods to improve attainable image quality at low field. We describe here the use of our end-to-end deep neural network approach (AUTOMAP) to improve the image quality of highly noise-corrupte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 39 publications
0
59
0
Order By: Relevance
“…While these dense layers enable data-driven learning of the manifold between k-space and the image domain, they also have significant memory requirements that make the translation to 3D reconstruction and tracking more challenging. [51,52] To perform reconstructions above the relatively low resolutions used for motion tracking on an MRI-Linac will require lighter-weight reconstruction networks. [18,53] One light-weight implementation of AUTOMAP is decomposed-AUTOMAP (dAU-TOMAP) which replaces dense layers with orthogonal 'domain transform' layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these dense layers enable data-driven learning of the manifold between k-space and the image domain, they also have significant memory requirements that make the translation to 3D reconstruction and tracking more challenging. [51,52] To perform reconstructions above the relatively low resolutions used for motion tracking on an MRI-Linac will require lighter-weight reconstruction networks. [18,53] One light-weight implementation of AUTOMAP is decomposed-AUTOMAP (dAU-TOMAP) which replaces dense layers with orthogonal 'domain transform' layers.…”
Section: Discussionmentioning
confidence: 99%
“…However, another valuable strength of data-driven MRI reconstruction models such as AUTOMAP is that they implicitly learn to suppress common MRI artifacts, such as spike noise caused by RF leakage, as these inputs typically fall outside the training domain. [52] The incorporation of new adversarial approaches into the training corpus will make neural network reconstructions more robust by identifying nonphysical input perturbations that can negatively impact reconstruction performance. [57,58] Our experiments with motion-encoded k-space demonstrated that as a highly over-parameterized model, AU-TOMAP has significant capacity to learn additional features.…”
Section: Discussionmentioning
confidence: 99%
“…There is little study in the literature on applying image reconstruction techniques to improve the quality of images from low-eld MRI scanners. These techniques include iterative methods like [14], dictionary learning methods like the approaches proposed in [46], [47], [48], and deep learning methods like AUTOMAP [74]. Experimental results from the literature revealed improved image quality of the reconstructed images.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, some studies used synthetic data in their experiments [75], [77], and therefore more experiments are using measured/real-world data. Studies using deep learning approaches in low eld MRI were very limited, during this study, we managed to identify and retrieve only two articles [74], [77]. However, deep learning approaches have been used for image reconstruction in high eld MRI [78].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For both, the problem of creating not necessarily large, but convincing 3D datasets has already been studied extensively, which also highlights the need for artificial test data in general. VascuSynth [9] is a popular tool (see [15], [16], [20], [36], [39]) for synthesis of arterial vessel trees, corresponding noisy volume data and segmentation based on oxygen demand maps. The software implementation [12], however, does not support out-of-core volume generation since it operates completely in memory.…”
Section: Introductionmentioning
confidence: 99%